The relative importance of cancer‐related and general health worries and distress among older adult, long‐term cancer survivors. Issue 2 (22nd October 2015) - Deimling, Gary T.; Brown, Sherri P.; Albitz, Casey; Burant, Christopher J.; Mallick, Nabeel
Abstract: Objective: This research examines the relative importance that cancer‐related and non‐cancer illness factors play in generating general health worries and/or cancer‐related worries. The analysis also examines how these in turn impact anxiety and depression among older adult, long‐term cancer survivors. Methods: Data from a longitudinal study of 245 older‐adult (age 60+ years), long‐term survivors (5 or more years after diagnosis) of breast, prostate, and colorectal cancer are examined to identify the measurement properties and structure of general health and cancer‐related health worries. Based on that measurement analysis, structural equation models (SEM) are used to estimate the relative importance of cancer‐related and other illness predictors on cancer‐related worry and general health worry and how these two forms of worry affect both anxiety (POMS) and depression (CES‐D). Results: The results from the exploratory and confirmatory factor analysis of health worries identify two relatively independent measures of health worry, one of general health worry and a second of cancer‐related worries that includes fears of recurrence, new cancers, and follow‐up testing. SEM analyses identified the importance of current cancer‐related symptoms and comorbidities on cancer‐related worry. It also documents the primacy of non‐cancer symptoms and general health worry as predictors of anxiety and depression among older survivors. Conclusions: The fact that cancer‐related symptoms continue to be associated with cancer‐related worries years after diagnosis speaks to the significance of these continuing sequelae. While the findings suggest the relative independence of cancer‐related worries and general health worries, both are correlated with anxiety and depression. This may be particularly problematic as survivors age and symptoms related to new health problems increase, while cancer‐related symptoms persist. Copyright © 2015 John Wiley & Sons, Ltd.